PENGARUH PERMAINAN TELEPON KALENG TERHADAP KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN DI TK NEGERI PEMBINA 3 KOTA PEKANBARU - Eva Nabila Andriana; Daviq Chairilsyah; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: Based on the result of observation in the field towards speaking ability of student, it find that speaking ability skill of student are not yet improve optimally. So, there is needed applying of cans phone game. This research has a purpose to know the influance of cans phone game. This Research of applying cans phone game skill of 4-5 years old children in Pembina 3 kindergarten of pekanbaru city. Sample of this research are 14 student of class A1. Technique to collage data is using observation technique and technique of data analysis is using t-test with using SPSS 18.0 program. Hypotheses of this research is there are very significant influance towards student speaking ability skill after applying cans phone game. This is knowing from the result of data combined t=21,337 p=0,000 because p < 0,05. So, it can be conclude that there has a very significant different of student speaking ability. Speaking ability skill after using cans phone game in teaching learning. So, its mean that Ho refused and Ha accepted that means there are very significant different between before and after doing the experiment with cans phone game. The effect of cans phone game skill of 4-5 years old children at pembina 3 kindergarten of pekanbaru city as much as 42,3%.Keyword: cans phone game,, speaking ability